Management of Long COVID—The CoviMouv' Pilot Study: Importance of Adapted Physical Activity for Prolonged Symptoms Following SARS-CoV2 Infection - Colas, Claire; Bayle, Manon; Labeix, Pierre; Botelho-Nevers, Elisabeth; Gagneux-Brunon, Amandine; Cazorla, Céline; Schein, Flora; Breugnon, Emma; Garcin, Arnauld; Feasson, Léonard; Roche, Frédéric; Hupin, David (Frontiers in Sports and Active Living, 2022)
Context After a COVID-19 infection, some patients have persistent symptoms, the most common is fatigue. To prevent it from becoming chronic (post-COVID-19 syndrome), early management before 3 months could be useful. Exercise and education are recommended. Objective To assess fatigue in patients with prolonged symptoms after COVID-19 infection and who received a mixed program of remote adapted physical activity and therapeutic education. The secondary objective was to evaluate the efficacy and safety of this training method thanks to aerobic and anaerobic parameters. Methods “CoviMouv': From Coaching in Visual to Mouv in real” is a nonrandomized controlled pilot study. Patients in telerehabilitation followed 12 remote exercise sessions and 3 therapeutic education workshops. Patients on traditional rehabilitation followed their program with a community-based physiotherapist. Results Fatigue was reduced after the one-month intervention in both groups (p = 0.010). The majority of aerobic parameters were significantly improved, e.g., maximal oxygen uptake (p = 0.005), walking distance (p = 0.019) or hyperventilation values (p = 0.035). The anaerobic parameter was not improved (p = 0.400). No adverse event was declared. Discussion Telerehabilitation is a good alternative when a face-to-face program is not possible. This care at an early stage of the disease could help prevent the chronicity of post-COVID-19 symptoms and the installation of vicious circles of physical deconditioning. A larger study would be necessary.